Nigeria-China Bilateral Relations:: Re-examining the Trajectory of the Nigerian Manufacturing Sector - Obikaeze, Chibuike Victor; Umo-Udo, Ndifreke S.; Nwokoye, Agary Ndubuisi; Daramola, Tunmise Oyindamola (Journal of Contemporary International Relations and Diplomacy, 2023)
Nigeria-China trade and investment relations are claimed to move to the advantage of China. Hence, the more their trade relation flourishes, the more Nigeria experiences trade deficits, and the more China records trade surpluses. In this scenario, Nigeria depends more on imports from China than China. That is why Nigerian market is overflowed with Chinese made products such as cell phones, television sets and so forth. The study examined how Nigeria-China relations impact on the manufacturing sector in Nigeria. The study employed secondary source of data collection and relied on ‘content analysis’ as a technique for data analysis. There has been recorded failure of Nigeria to compete favourably with China in terms of import and export of manufactured products. The manufacturing sector in Nigeria remains far behind to commensurately compete with China’s. Over concentration on the oil sector is directly linked to over reliance of the Nigerian economy on oil sector. The study draws a paradigm shift from the argument that China relations with Nigeria is imperialistic, to a hypothesis that the failure of the Nigerian government to adequately reposition Nigerian manufacturing to a globally competitive status through research and development as well as human capacity building, is thus, mainly responsible. The disarticulated economic structures Nigeria is currently maintaining is less capable of guaranteeing the development of the manufacturing sector that can enjoy competitive advantages in the international markets. Policy actions that are geared towards human capacity building and provision of sustainable incentives to local investors are needed.